2012
DOI: 10.1080/02642069.2011.574273
|View full text |Cite
|
Sign up to set email alerts
|

‘Balanced Scorecard’ as an operation-level strategic planning tool for service innovation

Abstract: This study proposes a model for implementing the balanced scorecard (BSC) as an operation-level strategic planning tool in a medical service department for service innovation. The study involved four major units in a district hospital: the internal medicine ward, surgery ward, gynecology ward, and pediatrics ward. The results indicated that the nursing department not only had its own unique goals and tasks, but also that it was obligated to a comprehensive service system in addition to its specific caring subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…In-depth discussions of the possibilities and controllability by middle managers in these subunits will ensure that top management understands the specific strategies of the business units as well as their limits of accountability. As an example, Luo et al (2012) explain how the use of strategy maps improved the BSC implementation in a medical service department. To ensure that the business unit strategies could contribute as much as possible to the corporate strategy, the middle managers were allowed to draft their own strategy map and BSC.…”
Section: Planningmentioning
confidence: 99%
“…In-depth discussions of the possibilities and controllability by middle managers in these subunits will ensure that top management understands the specific strategies of the business units as well as their limits of accountability. As an example, Luo et al (2012) explain how the use of strategy maps improved the BSC implementation in a medical service department. To ensure that the business unit strategies could contribute as much as possible to the corporate strategy, the middle managers were allowed to draft their own strategy map and BSC.…”
Section: Planningmentioning
confidence: 99%
“…PMSs effectiveness as a driver of positive organizational performance has been measured both in terms of process improvement and innovation (Luo et al, 2012), and increasing of final results.…”
Section: Measure Of the Outcomementioning
confidence: 99%
“…As a result of the prediction of nursing care hours (system, type of hospital, and geographic location), it is found that patient and nursing care hours are significantly related to the clinical data. Luo et al (2012) however, proposed a model for BSC implementation for service innovation. The study is designed for a medical service department and the implementation is based on an operation-level strategic planning tool while they studied internal medicine ward, surgery ward, gynecology ward, and pediatrics ward in a district hospital.…”
Section: Medical and Healthcarementioning
confidence: 99%